Respostas
respondido por:
1
f(x) = 2x² - 5
a) f(1)
f(1) = 2.(1)² - 5
f(1) = 2.1 - 5
f(1) = 2 - 5
f(1) = -3
b) f(1/2)
f(1/2) = 2(1/2)² - 5
f(1/2) = 2.(1/4) - 5
f(1/2) = 2/4 - 5
f(1/2) = (2-20)/4
f(1/2) = -18/4
f(1/2) = -9/2
Espero ter ajudado.
a) f(1)
f(1) = 2.(1)² - 5
f(1) = 2.1 - 5
f(1) = 2 - 5
f(1) = -3
b) f(1/2)
f(1/2) = 2(1/2)² - 5
f(1/2) = 2.(1/4) - 5
f(1/2) = 2/4 - 5
f(1/2) = (2-20)/4
f(1/2) = -18/4
f(1/2) = -9/2
Espero ter ajudado.
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás